Awareness, anxiety and coping regarding COVID-19 among South Indian population: web based cross sectional survey - Kanagaraj, Puvaneswari; Kanagaraj, Anbueswari; Srinivasan, Madhusheela; Jacob, Jessy; Philip, Mariamma (International Journal Of Community Medicine And Public Health, 2020)
Background: COVID-19, a highly infectious pandemic illness, has caused stress in everyone globally. It is a new situation, where no one is prepared to battle. With the currently available data, health care and the government makes guidelines and fights against this pandemic. The cooperation of the public is highly important to prevent and control the spread of COVID-19. Methods: A web based cross-sectional survey was conducted among 519 participants using convenience snowballing technique to assess the awareness, anxiety, and coping strategies regarding COVID-19 from 14 May 2020 to 24 May 2020. The validated online Google form questionnaire consisted of demographic variables, questionnaire related to awareness on COVID-19, anxiety related to COVID-19, and coping strategies. The analysis was done using both the descriptive and inferential statistics. Results: The majority of them were graduates and postgraduates. And 78% of them reported that no COVID-19 positive cases were identified in their area. The awareness score was 7.47±1.37 (median=8, range: 1-10). And the overall anxiety regarding COVID-19 was 47.74±11.58 (Range 17-85). On average, participants practiced 4 coping strategies ranged from 1-8 mainly ‘talking to friends and family’ and ‘taking care of diet’. Awareness was positively correlated with behavioral anxiety (r=0.103, p=0.019) and the number of coping strategies used (r=0.146, p=0.001). Conclusions: The study showed that awareness was positively associated with hand washing, social distancing which are the parts of preventive activities. Health promotion activities in terms of health education can improve the behavioural change.